Effect of mass sports activity on prosocial behavior: A sequential mediation model of flow trait and subjective wellbeing - Duan, Xiyan; Wang, Xiaohua; Li, Xiaogang; Li, Shichen; Zhong, Yiping; Bu, Te (Frontiers in Public Health, 2022)
Objectives: Participation in mass sports is one of the most efficient strategies for people to attain physical and mental health in China. Prosocial behavior has a positive effect on social development. This study developed a conceptual model with mass sports activity as the independent variable, prosocial behavior as the dependent variable, and flow trait and subjective well-being as the mediating variables. Methods: Participants (N = 351) completed an online survey. Mass sports activity, flow trait, subjective well-being, and prosocial behavior were measured using the physical activity rank scale-3 (PARS-3), short dispositional flow scale (SDFS), index of well-being (IWB), and prosocial tendencies measure (PTM), respectively. Descriptive statistics compared differences between sports population (PARS-3, ≥ 36) and non-sports population (PARS-3, < 36). Mediation effect was analyzed using the PROCESS (Template, Model 6). Results: Sports population scored significantly higher (all P ≤ 0.05) on SDFS, IWB, and PTM than non-sports population. Participation in mass sports stimulated flow trait and thus improved prosocial behavior, with a mediation effect value of 0.061 (95% CI, 0.028 to 0.104), which accounted for 30.18% of the total effect. Participation in mass sports enhanced subjective well-being and thus improved prosocial behavior, with a mediation effect value of 0.044 (95% CI, 0.007 to 0.090), which accounted for 21.96% of the total effect. Flow trait and subjective well-being mediated the relationship between mass sports activity and prosocial behavior in a sequential manner, with a mediation effect value of 0.059 (95% CI, 0.035 to 0.090), which accounted for 29.23% of the total effect. Conclusion: The preliminary results of the mediation model validated the hypothesized sequential links between mass sports activity, flow trait, subjective well-being, and prosocial behavior. Greater participation in mass sports increases the likelihood of prosocial behavior.